Inter-charity competition under spatial differentiation: sorting, crowding, and spillovers - Gallier, Carlo; Goeschl, Timo; Kesternich, Martin; Lohse, Johannes; Reif, Christiane; Römer, Daniel (Journal of economic behavior & organization, 2023)
We study spatially differentiated competition between charities in a framed field experiment. We introduce spatial differentiation by varying the observability of charities’ location such that each donor faces a socially close ‘home’ and a socially distant ‘away’ charity. In our field setting, we observe spatially differentiated competition between charities offering the same good to be characterized by sorting, crowding-in, and an absence of spill-overs: Donors sort themselves by distance; fundraising (through matching) for one charity raises checkbook giving to that charity, irrespective of spatial distance; but checkbook giving to the unmatched charity is not affected.